Process Monitoring in Andhra Pradesh : An Award-Winning Innovation in Project Supervision - Shah, Parmesh (World Bank, Washington, DC, 2012)
This note explains that given the limited budgets allocated to supervision activities, supervising World Bank projects has long been a serious challenge-particularly in sprawling rural areas with small poor communities spread out over vast distances. Innovative ways of sharing monitoring and supervision roles and responsibilities with local partners, therefore, carry important practical implications for project managers, whose own capacity to monitor developments and identify challenges is limited by distance and time constraints.